Dimensions of international entrepreneurship: an analysis of texts in a business magazine - Castro, Ãlvaro Leonel de Oliveira; Pereira, Michele Morais Oliveira; Silva, Francielih Dorneles; Andrade, Daniela Meirelles (Revista de Negócios, 2020)
This study analyzed texts on international entrepreneurship published in the Exame magazine from the perspective of Leite and Moraes’ framework (2014). We used the technique of content analysis in 78 texts. The categories were a tendency to adapt; relationship networks; international opportunities; ability to innovate; attitude towards risk; development of competitive resources. All the model categories were approached in the analyzed articles, indicating that the dimensions proposed are part of the international entrepreneurship phenomenon and that the business professionals who read the magazine are being informed about this content. From the managerial and social aspects, this work showed that the Exame Magazine has informed about global business to business professionals, through the cases in their reports. It demonstrates that it can be an important means of the initial information for them, since, from those experiences, it presents the complexity and main characteristics of international entrepreneurship found in the scientific literature.